Rejuvenation of spiral bulges - Thomas, D; Davies, R (2005)
We seek to understand whether the stellar populations of galactic bulges show fingerprints of secular evolution triggered by the presence of the disc. For this purpose we re-analyse the sample of Proctor and Sansom, deriving stellar population ages and element abundances from absorption line indices. We obtain very consistent constraints on ages from the three Balmer indices Hbeta, Hgamma, and Hdelta, in good agreement with those of Proctor and Sansom based on a completely different method. Like other studies in the literature, we find that bulges have relatively low luminosity weighted ages, the lowest age derived for the smallest bulges being 1.3 Gyr. Hence bulges are not generally old but actually rejuvenated systems. We discuss evidence that this might be true also for the bulge of the Milky Way. We show that the smallest bulges, being the youngest with the lowest alpha/Fe ratios, must have experienced star formation events involving 10-30 per cent of their total mass in the past 1-2 Gyr. No significant correlations of the stellar population parameters with Hubble Type are found instead. We show that the relationships with sigma coincide perfectly with those of early-type galaxies. Hence, bulges are typically seen younger, metal-poorer and less alpha/Fe enhanced than early-type galaxies, only because of their smaller masses. At a given velocity dispersion, bulges and elliptical galaxies are indistinguishable as far as their stellar populations are concerned. These results favour an inside-out formation scenario and indicate that the discs in spiral galaxies of Hubble types Sbc and earlier cannot have a significant influence on the evolution of the stellar populations in the bulge component. The phenomenon of pseudobulge formation must be restricted to spirals of types later than Sbc.